Sesquiterpenes from the rhizomes of curcuma ochrorhiza - Mohd. Sirat, Hasnah (Natural Product Communications, 2009)
From the rhizomes of Curcuma ochrorhiza, four sesquiterpenes, isofuranodiene, germacrene, furanogermenone and zederone, have been isolated, the structures of which have been elucidated by spectroscopic methods.